Evaluation of the Indonesia Population Administration Awareness Movement (GISA) programme in Bogor Regency - Jakaria, Muhammad Jejen; Maruapey, Muhamad Husein; Rusliandy (MultiTech Publisher, 2024)
This research is entitled Evaluation of the Indonesian Population Administration Awareness Movement (GISA) Programme in Bogor Regency. The purpose of this research is to evaluate and find out the obstacles encountered in the implementation of the GISA Programme in Bogor Regency. This is motivated by the low level of public awareness of the importance of having legal population documents in accordance with the law. This research uses descriptive qualitative methods and uses evaluation theory according to William N Dunn with its criteria indicators, namely Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Appropriateness. Data collection techniques use primary and secondary data sources, namely primary data sources including observation and interviews while secondary data sources with literature studies and documentation are then combined for validity using triangulation techniques. For data analysis using the Miles and Huberman model, namely by collecting data, reducing data, presenting data, then drawing conclusions. The results obtained show that the desired results are not quite optimal. This is due to the obstacles faced, including distance that causes limited access and information, limited resources, lack of coordination between agencies, and also the presence of brokers who often harm the community. There needs to be binding or compelling rules, in addition to the awareness of all parties to make a real contribution in an effort to improve the quality of population administration services so that all matters relating to population data can be resolved so that the realisation of an orderly national population administration in accordance with the laws and regulations